Efektivitas Media Video Animasi dalam Pembelajaran Sosiologi terhadap Peningkatan Pemahaman Materi Peserta Didik pada SMAN 12 Merangin - Friska Ayuliandari; Ike Sylvia (Universitas Negeri Padang, 2022)
The development of the era which has entered the 21st century, science and information technology is growing very rapidly has a lot of influence on all areas of life. Especially in the educational aspect, the use of technology can be applied in the learning process in schools, namely by using learning media. The purpose of this research is to help students understand the material and relate the concepts of sociology learning in everyday life. This study uses an experimental method with a one group pretest-posttest research design. Data collection was carried out with a question instrument in the form of a pretest posttest. The target of the trial in this study was in class XI IPS 2 at SMA N 12 Merangin using purposive sampling as an experimental class with 32 students as research subjects. After testing the normality and homogeneity tests for data analysis of the effectiveness of the sociology learning animation video media, the t-test was carried out. Based on the results of the study showed that animated videos in sociology learning proved to be effective.